An effective restoration of one-carbon metabolism in folate-deficient mice with a high-folate corn inbred line. (December 2022) - Lu, Xiaolin; Jiang, Ling; Zhang, Qizong; Huo, Junshen; Min, Jie; Liang, Qiuju; Zhao, Lijiao; Li, Yan; Chang, Shaoyan; Zhang, Ting; Zhang, Chunyi; Wang, Li
Graphical abstract: Highlights: Folate-supplementation restored folate deficiency status in 4 weeks. Restoration effect varies depending on different FA sources. Orderly phospholipid metabolism implies a healthy status under FHC supplementation. Abstract: Since folic acid (FA) was officially recommended in 1998, concerns have emerged about the effect of excess FA intake, in particular with respect to negative clinical effects. Given this, a high-folate corn inbred line that we identified from a global germplasm collection was believed to become a valid alternative to FA supplementation. In this study, we proved this natural form of plant-sourced folates exhibited an effective restoration of folate deficiency. Folate metabolism and methylation modifications were restored in folate-deficient mice with folate-supplemented diets in 4 weeks. Restoration effects varies depending on folate sources, restricted retrotransposon activity and an orderly pattern of phospholipid/lipid metabolism protected by this high-folate corn partly ensures a healthy folate status for development. Totally, we proved in mice models that this kind of folate biofortification corn could provide a valid alternation of FA supplementation in alleviation of folate deficiency during pregnancy.